2012
DOI: 10.1051/0004-6361/201219559
|View full text |Cite
|
Sign up to set email alerts
|

Searching for planetary-mass T-dwarfs in the core of Serpens

Abstract: Context. The knowledge of the present-day mass function of young clusters and the mass of their coolest substellar members is essential to clarify the brown dwarf formation mechanism, which still remains a matter of debate. Aims. We searched for isolated planetary-mass T-dwarfs in the ∼3 Myr old Serpens Core cluster. Methods. We performed a deep imaging survey of the central part of this cluster using the WIRCam camera at the CFHT. Observations were performed through the narrow-band CH 4 off and CH 4 on filter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…2 Jacob Ward, Joana Oliveira, Jacco van Loon, Marta Sewilo In general our sample exhibits high Brγ luminosities / K -band magnitude ratios compared with similar objects in the Milky Way from Cooper et al (2013), suggestive of higher accretion rates. This would be consistent with the results of De Marchi et al (2011) and Spezzi et al (2012), finding that low mass pre-main sequence stars exhibit higher accretion rates in the Magellanic Clouds than in the Milky Way. The effects of metallicity on H i emission are expected to be small (Kudritzki 2002) and we see no excess He i emission compared to the Galactic sample.…”
Section: Introductionsupporting
confidence: 92%
“…2 Jacob Ward, Joana Oliveira, Jacco van Loon, Marta Sewilo In general our sample exhibits high Brγ luminosities / K -band magnitude ratios compared with similar objects in the Milky Way from Cooper et al (2013), suggestive of higher accretion rates. This would be consistent with the results of De Marchi et al (2011) and Spezzi et al (2012), finding that low mass pre-main sequence stars exhibit higher accretion rates in the Magellanic Clouds than in the Milky Way. The effects of metallicity on H i emission are expected to be small (Kudritzki 2002) and we see no excess He i emission compared to the Galactic sample.…”
Section: Introductionsupporting
confidence: 92%
“…This is the goal of a large programme (P.I. J. Bouvier) we are conducting at the Canada-France-Hawaii Telescope (CFHT), designed to uncover the substellar population of various nearby young clusters and compare their IMF and minimum mass for brown dwarf formation (Burgess et al 2009;Alves de Oliveira et al 2010;Alves de Oliveira et al 2012;Spezzi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alves de confirmed spectroscopically the first L dwarfs in the ρ Ophiuchus molecular cloud with masses between 10 and 4 MJup, resulting in a mass function in agreement with other regions (Bastian et al 2010) and the field (Chabrier 2003(Chabrier , 2005. Moreover, Spezzi et al (2012) reported two potential T-type candidates in the core of the Serpens cloud with masses of a few Jupiter masses if true members. Similarly Burgess et al (2009) identified one mid-T-type candidate in IC 348 with a mass between 5 and 1 MJup but spectroscopy is mandatory to confirm their nature.…”
Section: Introductionmentioning
confidence: 99%